Broken Compass: A Screenplay Exploring Economic Inequality in Indonesia’s Education System - Maria Inosensia Laymonita; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
Good quality education should be accessible to everyone, regardless of their economic status. Unfortunately, often better education in Indonesia comes with a heavy price tag that eliminates working class people from accessing it. This thesis attempts to find out why the working class people are economically discriminated and how they face the discrimination. Using screenplay and young adult dystopian genre, this thesis tries to show the side effects of said economic inequality if taken to the extreme. With Pierre Bourdieu’s theory of school as cultural reproduction, the working class students, including the protagonist Thalia, are discriminated against because they are seen as threats to their resources. To reciprocate, Thalia challenges the system, which sparks a rebellion inside the school. The worldbuilding aspect of the genre is based on Pierre Bourdieu's concepts of social space, capitals, and agency. Thalia from the working class utilizes her agency to face the discrimination.